Neutrophil Functions in Immunodeficiency Due to DOCK8 Deficiency. (19th May 2019) - Mandola, Amarilla B.; Levy, Jacov; Nahum, Amit; Hadad, Nurit; Levy, Rachel; Rylova, Anna; Simon, Amos J.; Lev, Atar; Somech, Raz; Broides, Arnon
ABSTRACT: Neutrophil chemotactic defects have been reported previously in patients with hyper-IgE syndrome. Bi-allelic mutations in dedicator of cytokinesis 8 (DOCK8) gene usually cause an autosomal recessive hyper-IgE syndrome phenotype. Data are lacking about expression of DOCK8 protein in neutrophils or the possible role of DOCK8 in neutrophil function. We sought to determine if DOCK8 protein is expressed in neutrophils and if DOCK8 plays a role in neutrophil function. The expression of DOCK8 protein was assessed in neutrophils from healthy volunteers with and without activators. Neutrophil chemotaxis, phagocytosis and superoxide generation were studied in neutrophils from DOCK8-deficient patients compared to neutrophils from healthy controls before and after stimulation with activators: phorbol 12-myristate 13-acetate (PMA) or N-Formylmethionyl-leucyl-phenylalanine (fMLP). DOCK8 protein is expressed in resting neutrophils from healthy controls, with a significant increase in DOCK8 expression after stimulation. Neutrophil functions were assessed in 6 DOCK8-deficient patients. All patients had the same non-sense mutation (c.C5134A, p.S1711X). Normal chemotaxis was recorded in 4/6 patients while a mild to moderate chemotaxis defect was recorded in 2/6. Superoxide generation was mainly normal in neutrophils from all six patients and phagocytosis was normal in five patients tested. We conclude that DOCK8 protein is expressed in resting human neutrophils and DOCK8 expression is increased after stimulation with either PMA or fMLP. Most patients with a disease-causing mutation in DOCK8 have normal neutrophil functions, while a minority showed a mild to moderate chemotactic defect.